Constraints on light decaying dark matter candidates from 16 yr of INTEGRAL/SPI observations. Issue 3 (14th February 2023) - Calore, F; Dekker, A; Serpico, P D; Siegert, T
ABSTRACT: We apply the recently developed analysis of 16 yr of INTEGRAL/SPI data including a dark matter spatial template to derive bounds on dark matter candidates lighter than weakly interacting massive particles (like sterile neutrinos or axion-like particles) decaying into line or continuum electromagnetic final state channels. The bounds obtained are the strongest to date for dark matter masses between ∼60 keV and ∼16 MeV experiencing two-body decays producing photon lines.